Household Energy Use and Determinants: Evidence from Nigeria - Ogwumike, Fidelis O.; Ozughalu, Uchechukwu M.; Abiona, Gabriel A. (International Journal of Energy Economics and Policy, 2014)
This study examined household energy use and its determinants in Nigeria based on the 2004 Nigeria Living Standard Survey data obtained from the National Bureau of Statistics. The study utilised descriptive statistics and multinomial logit models. Most households in Nigeria use firewood as cooking fuel and kerosene for lighting. This shows that most Nigerian households do not have adequate access to environmentally-friendly modern energy sources. Energy use in Nigeria supports fuel stacking rather than energy ladder hypothesis. Among the factors that significantly influence household energy use for cooking are educational levels of father and mother, per capita expenditure and household size. Adequate measures should be taken to ensure that most households in Nigeria have access to modern environmentally-friendly sources of energy. This will pave the way for sustainable development in the country. The results of this study should serve as an invaluable guide to the Nigerian government and policymakers. Keywords: Energy use; Multinomial logit; Poverty; Determinants; Nigeria. JEL Classifications: I32; Q40; R20